2015
DOI: 10.1186/s12936-015-0753-9
|View full text |Cite
|
Sign up to set email alerts
|

Malaria elimination in Haiti by the year 2020: an achievable goal?

Abstract: Haiti and the Dominican Republic, which share the island of Hispaniola, are the last locations in the Caribbean where malaria still persists. Malaria is an important public health concern in Haiti with 17,094 reported cases in 2014. Further, on January 12, 2010, a record earthquake devastated densely populated areas in Haiti including many healthcare and laboratory facilities. Weakened infrastructure provided fertile reservoirs for uncontrolled transmission of infectious pathogens. This situation results in un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 53 publications
2
50
0
1
Order By: Relevance
“…Seven samples from patients with infections acquired in the Dominican Republic in 2015 were tested for molecular resistance markers, and none contained a genotype associated with chloroquine resistance. Haiti and the Dominican Republic intend to eliminate malaria transmission on the island of Hispaniola by 2020 ( 81 , 82 ); therefore, the number of cases from both countries is expected to decrease. However, as indicated by the increase in cases in 2015, transmission on the island remains heterogeneous, and malaria cases could begin to increase if efforts to contain transmission are weakened.…”
Section: Discussionmentioning
confidence: 99%
“…Seven samples from patients with infections acquired in the Dominican Republic in 2015 were tested for molecular resistance markers, and none contained a genotype associated with chloroquine resistance. Haiti and the Dominican Republic intend to eliminate malaria transmission on the island of Hispaniola by 2020 ( 81 , 82 ); therefore, the number of cases from both countries is expected to decrease. However, as indicated by the increase in cases in 2015, transmission on the island remains heterogeneous, and malaria cases could begin to increase if efforts to contain transmission are weakened.…”
Section: Discussionmentioning
confidence: 99%
“…Casi el 80% de toda la población tiene acceso a las prácticas de una medicina complementaria ampliamente extendida, en tanto que la medicina moderna con frecuencia es el último recurso frente a una enfermedad, especialmente para quienes viven en sectores rurales, dependiendo de su educación y de sus convicciones religiosas 10,11 . La malaria es endémica y Haití concentra el mayor número de casos en ALC (17.696 casos el año 2014), que ha sido difícil de erradicar por las propias condiciones de salud y geografía 13,14 . La prevalencia de tuberculosis (TBC) no es fácil de estimar ya que organizaciones externas financian los programas de tratamiento.…”
Section: La Salud En Haitíunclassified
“…In Ethiopia, shortage of staff, capacity and motivation were identified as key issues likely to threaten the country’s goal of eliminating malaria by 2020 [18]. In Haiti, the meeting of stakeholders comprising laboratory personnel, researchers, clinicians, academics and public health professionals concluded that additional healthcare worker training and the deployment of critical resources were key to achieving the goal of eliminating malaria by 2020 [19]. Sri Lanka, which is now eligible to apply for the WHO (World Health Organization) elimination certification, had its elimination plans in the 1960s frustrated by stakeholders’ complacency, whereby patients with fever were not tested for malaria as a result of physicians’ inertia [5,20].…”
Section: Introductionmentioning
confidence: 99%